Exploring Tourists’ Intentions to Adopt Augmented Reality in Cultural Heritage Museums: Insights From a Modified Technology Acceptance Model - Wenjing Xu; Mazran Ismail; Syafizal Shahruddin; Wen Quan; Yingrui Li (SAGE Open)
Augmented reality (AR) adoption in archeological site museums has attracted growing attention; however, a notable gap remains in understanding how personal traits and technological perceptions interact to influence tourists’ choices. To address this gap, this study conducted at the Sanxingdui Archeological Site Museum employs the Technology Acceptance Model (TAM), a widely used framework for analyzing user acceptance of technology, alongside structural equation modeling to examine the nuanced interplay of Technology Readiness dimensions and their impact on perceptions. The findings reveal that optimism does not significantly influence attitudes toward AR, while innovativeness has a positive effect. Discomfort is negatively associated with AR attitudes, while perceived security concerns have a counterintuitive positive effect. Moreover, perceived ease of use strongly determines the perceived usefulness of AR, which, in turn, directly influences attitudes toward the technology. Perceived ease of use also plays a crucial role in shaping AR attitudes. Additionally, a positive attitude toward AR is strongly linked to future adoption intentions, which, in turn, significantly correlate with tourists’ intentions to visit destinations. These insights not only enhance academic discussions on TAM and AR in tourism but also offer valuable practical implications for the museum sector seeking seamless AR integration.